ΚG-Contractive Mappings in Fuzzy Metric Spaces. (26th February 2022) - Samreen, Maria; Hussain, Sharafat; Aydi, Hassen; Ulrich Gaba, Yaé
Abstract : This article is concerned with a class of contractions in the framework of a fuzzy metric space endowed with a graph. The main results obtained not only broaden but also generalize a number of relevant results in the literature. Particularly, we get some results for cyclic contractions in fuzzy metric spaces. We also consider an integral equation.